Analisis Dampak Pertumbuhan Penduduk Kota Batam Dalam Pembangunan Daerah - Milenisha Andani; Karol Teovani Lodan; Dompak, Timbul (Prodi Ilmu Administrasi Negara, 2024)
Abstract: Development is the scope of the entire process of change where the definition of change here is related to all aspects of people's lives, both in the fields of politics, economy, socio-culture, infrastructure, education and technology. Development is certainly not just about building infrastructure but development also refers to an action in the sense of creating and producing a government program in promoting welfare, prosperity, and providing good development for the growth of a region. If the development process can run well, the country's economic system will also improve and will be much more prosperous when the development of the region is prepared in a planned and well-implemented manner. However, if the course of regional development is accompanied by fairly dense population growth, the development process will be hampered, this is also due to the impact given by dense population growth. This study uses a descriptive method which is used to describe a situation that occurs and explain the situation through the impacts that exist due to population growth on regional development. Keywords: Population Growth, Regional Development